Effects of Anakinra on Health-Related Quality of Life in a Patient with 1129G>A/928G>A Mutations in MVK Gene and Heterozygosity for the Mutation 2107C>A in CIAS1 Gene - Gianluigi Laccetta; Maria Tutera; Mario Miccoli; Rita Consolini (Frontiers Media S.A., 2017)
Mevalonate kinase deficiency impairs several aspects of the patient's quality of life, thus early diagnosis and treatment are required to improve health-related quality of life (HRQOL). A 15-year-old patient with double heterozygosity for the mutations 1129G>A and 928G>A in MVK gene, heterozygosity for the mutation 2107C>A in CIAS1 gene and hyper-IgD syndrome phenotype, has been treated with anakinra with a reduction of 50% in the number of fever episodes per month, a reduction of 33% in the days of fever for each attack and normal blood tests in the intercritical phase. The RAND 36-Item Health Survey has been used for the assessment of HRQOL before and after the treatment with anakinra. The patient's quality of life showed an overall improvement of 27%; results showed a better improvement in role limitations due to physical health (50%).